Clonagem e caracterização molecular da fosforribosil pirofosfato sintase (PRPP sintase) de cana-de-açucar - Sculaccio, Susana Andréa (Universidade Federal de São Carlos, 2002)
Phosphoribosylpyrophosphate synthetase (PRS - EC: 2.7.6.1) is an enzyme of central importance in several metabolic pathways in all cells. So far the plant PRS enzymes have not been investigated in great detail. However, accumulated evidences indicate that those enzymes form a complex family of isoenzymes with subcellular localization (mitochondria, cytoplasm and nucleus) and different phosphate dependence characteristics. The prs gene was cloned and had the sequence determined from a sugarcane cDNA library clone identified by the plant genome effort (SUCEST). The sugarcane prs gene contains a 984 bp open reading frame that encodes 328 amino acids protein with a calculated molecular weight of 36.6 kDa. The predicted amino acid sequence has 77 and 78% amino acid identity to the PRS4 of Arabidopsis thaliana and Spinacia oleracea respectively. The phylogenetic reconstruction of selected PRS homologues indicates that this enzyme may be a phosphate-independent PRS isoenzyme. The PRS protein was expressed in Escherichia coli, purified to homogeneity and found to retain secondary structure elements and quaternary arrangement consistent with the known PRS homologues. The availability of the PRS enzyme from another plant and the possibility of expressing the protein in large quantities should provide the basis for a functional and structural analysis of this important enzyme.
Keywords: Biologia molecular; Clonagem; Biosíntese; Purinas; Fosforribosil pirofosfato; CIENCIAS BIOLOGICAS::GENETICA